Reproductive hormonal variations and adenohypophyseal lesions in pre-pubertal buffalo heifers inoculated with Pasteurella multocida type B: 2 and its immunogens - Abdullah, Faez Firdaus Jesse; Ibrahim, Hayder Hamzah; Abba, Yusuf; Lim, Eric Teik Chung; Marza, Ali Dhiaa; Mazlan, Mazlina; Saad, Mohd Zamri; Omar, Abdul Rahman; Abu Bakar @ Zakaria, Md Zuki; Saharee, Abdul Aziz; Haron, Abd Wahid; Mohd Lila, Mohd Azmi (BioMed Central, 2017)
BACKGROUND: Hemorrhagic septicemia is a fatal disease of cattle and buffaloes caused by P. multocida. Although the pathogenesis of the bacteria has been well established in literature, there is a paucity of information on the possible role of the bacteria and its immunogens; lipopolysaccharide (LPS) and outer membrane proteins (OMPs) on the reproductive capacity of buffalo heifers. METHODS: In this study, twenty one healthy prepubertal female buffaloes aged 8 months were divided into seven groups of 3 buffaloes each (G1-G7). Group 1 (G1) served as the negative control group and were inoculated orally with 10 mL sterile Phosphate Buffer Saline (PBS), groups 2 (G2) and 3 (G3) were inoculated orally and subcutaneously with 10 mL of 1012 colony forming unit (cfu) of P.multocida type B: 2, while groups 4 (G4) and 5 (G5) received 10 mL of bacterial LPS orally and intravenously, respectively. Lastly, groups 6 (G6) and 7 (G7) were orally and subcutaneously inoculated with 10 mL of bacterial OMPs. Whole blood was collected in EDTA vials at stipulated time points (0, 2, 4, 6, 8, 10, 12, 24, 36, 48, 72, 120, 168, 216, 264, 312, 360, 408, 456 and 504 h), while tissue sections of the pituitary glands were collected and transported to the histopathology laboratory in 10% buffered formalin for processing and Hematoxylin and eosin staining. Plasma levels of luteinizing hormone (LH), follicle stimulating hormone (FSH), progesterone (PG), estradiol (EST) and gonadotrophin releasing hormone (GnRH) were determined. RESULTS: The histopathological lesions observed in the pituitary gland included hemorrhage, congestion, inflammatory cell infiltration, hydropic degeneration, necrosis and edema. These changes were higher (p < 0.05) in distribution and severity in G3, G6 and G7. Hormonal concentrations of LH, FSH, PG, EST and GnRH declined in all inoculation groups as time elapsed and were lower (p < 0.05) than that of the control group. CONCLUSION: Based on these findings, P.multocida B: 2 and its immunogens can be said to negatively affect the hypothalamic-pituitary-gonadal axis, resulting in decreased levels of reproductive hormones which may predispose to infertility in buffalo heifers.